Last papers in linguistic historiography - Koerner, E. F. K. (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 2020)
"This volume brings together, in 8 chapters, what has occupied the author during his many years as editor of Historiographia Linguistica. Namely, how the history of linguistics has developed into a major field of scholarly research, and that the discussion of questions of method and epistemology needs to be continued to avoid stereotypical practice. The author takes up a number of subjects that often had been regarded as settled, but which require a revisit. This is shown in several chapters, whether it appears subjects like 'analogy' or the relationships between well-known linguists like Saussure, Hermann Paul, and others"--